2015
DOI: 10.1021/jp5127915
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical Investigation of Shape-Designed MnO2 Nanostructures and Their Influence on Oxygen Reduction Reaction Activity in Alkaline Solution

Abstract: In this work, five types of MnO 2 nanostructres (nanowires, nanotubes, nanoparticles, nanorods, and nanoflowers) were synthesized with a fine control over their α-crystallographic form by hydrothermal method. The electrocatalytic activities of these materials were examined toward oxygen reduction reaction (ORR) in alkaline medium. Numerous characterizations were correlated with the observed activity by analyzing their crystal structure (TGA, XRD, TEM), material morphology (FE-SEM), porosity (BET), inherent str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 81 publications
3
62
1
Order By: Relevance
“…The strong absorption at 3410 cm −1 attributed to the stretching vibration of O−H which may arises from adsorbed water. Similarly, the strong broad band at 570 to 635 cm −1 in Raman spectra was correlated to the nature of the tunnel species and it belongs to A g spectroscopic species that originate from the breathing vibration of MnO 6 octahedra within a tetragonal framework . The N 2 ‐sorption studies (Figure S3) were showed a type IV isotherm with H1 hysteresis loop which further confirms the porous nature and ordered arrangement in the materials.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The strong absorption at 3410 cm −1 attributed to the stretching vibration of O−H which may arises from adsorbed water. Similarly, the strong broad band at 570 to 635 cm −1 in Raman spectra was correlated to the nature of the tunnel species and it belongs to A g spectroscopic species that originate from the breathing vibration of MnO 6 octahedra within a tetragonal framework . The N 2 ‐sorption studies (Figure S3) were showed a type IV isotherm with H1 hysteresis loop which further confirms the porous nature and ordered arrangement in the materials.…”
Section: Resultsmentioning
confidence: 63%
“…In the recent years, many studies have been focused on the development of bifunctional electrodes based on non‐precious materials like metal oxides, carbon supported materials and hybrid materials, by adapting different structural modifications . Among the oxides materials, manganese oxide create a center of attention more due to the merits of natural abundance, low toxicity, structural diversity and multi valance nature . It has the potential to impact in various fields like catalysis,, supercapacitors,, and metal‐air batteries, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, the Raman peak at 565.5 cm À1 can be attributed to the symmetric stretching vibration (MneO) of MnO 2 [20,21], indicating the existence of MnO 2 in the composite foam, too. Furthermore, there presents a new Raman peak at 1100 cm À1 , which may be attributed to the interaction between rGO and MnO 2.…”
Section: Resultsmentioning
confidence: 84%
“…So, the development of MnO 2 /rGO nanocomposite materials could draw on each other's merits and raise the level together for the both electrode materials. Currently, many strategies have been developed for the synthesis of MnO 2 /rGO nanocomposites, such as hydrothermal route [16], solution phase approach [17,18], solidestate reaction approach [19], chemical precipitation approach [20,21], and microwave heating approach [22]. However, products generated by the most methods were often in powder composite type.…”
Section: Introductionmentioning
confidence: 99%
“…Samples S0 , S0.2 , S0.02 and S0.002 previously identified as MnO 2 , were further confirmed to present a αMnO 2 structure by Raman scattering. αMnO 2 presents two (2) vibrational diagnostic bands in the region of 570 and 640 cm −1 corresponding to A g spectroscopic species originating from breathing vibrations of MnO 6 octahedra within a tetragonal hollandite‐type structure . These two bands are present in all the aforementioned samples.…”
Section: Resultsmentioning
confidence: 95%